Understanding International Economic Issues Amidst Changing Global Landscape. - Schwalbenberg, Henry (Foreign Affairs)
Fordham University's Master's Program in International Political Economy and Development (Fordham IPED) offers a unique and rigorous approach to analyzing global economic relations. The program emphasizes understanding international economic issues from both political and economic perspectives, and provides students with strong quantitative skills in data analysis and computer programming. Fordham IPED prepares students to anticipate and adapt to changes in the international affairs landscape, including climate change and technological innovations like artificial intelligence. The program's location in New York City provides students with internship opportunities at organizations such as the United Nations and Wall Street, and its small class size allows for close interactions with faculty. Fordham IPED has a strong alumni network and a record of placing graduates in various sectors, including the private sector, nonprofit sector, government, and academia.